ANALISIS PEMBEBANAN BIAYA OVERHEAD TERHADAP HARGA JUAL WAROENG IBU NOENG DI BEKASI - Wawan Haryanto (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2018)
The current global era of economic conditions in Indonesia is indeed very alarming since the economic crisis that hit the Indonesian nation made many people lose their jobs and unemployment. Many crimes occur everywhere, especially in big cities like Jakarta, many entrepreneurs go bankrupt then go bankrupt, many teenagers have to drop out of school and become unemployed, as creative citizens we should not be discouraged or even give up on the present situation which is difficult and we must try, be creative, innovative and dare to take a decision and risk to create jobs alone, we do not have to depend on others, to get a job we have to do everything possible. Based on the results of the study using Analysis of Waroeng's Descriptive Method Mrs. Noeng showed that the results obtained a profit of Rp. 9,685,000 /month and a day had to produce Rp. 312,419 / day with minimum sales of 21 Provisions/day and minimum operating profit was set at least 20% of the total costs incurred opportunities for business are planned for 20,315,000X 20%: IDR 4,063,000. company BO tariff calculation treatment can precisely set the product selling price so that the company can maintain the survival of the company (the Going Concern Concept) to be able to survive long amid difficult economic conditions and intense competition This research was conducted at Waroeng Ibu Noeng in Bekasi selling Fried Chicken Duck and Chicken Noodle Meatballs.